Determinants of Corporate Bond Rating in Indonesia: Additional Evidence - Utami, Elok Sri; Anitasari, Diah; Endhiarto, Tatok (Review of Management and Entrepreneurship, 2018)
This study examines the determinants of bond rating of companies in Indonesia. Four variables are examined, namely profitability ratio, liquidity ratio, solvency ratio, and activity ratio. The sample consists of 15 companies over the period of 2011-2014. It uses logistic regression analysis method to test the effect of the independent variables on the dependent variable. Results show that only liquidity ratio has significant influence on bond ratings. Profitability, solvency, and activity ratios are found not to be the significant determinants of the companies’ bond ratings.